A Novel Tolerance-Based Moderator Guided Heterogeneous Group Decision-Making Involving Experts and End-Users - Singh M.; Baranwal G.; Tripathi A.K. (My University, 2025)
This study focuses on two issues of group decision-making (GDM). First, the multiple rounds of feedback recommendations in the consensus reaching process (CRP) make GDM inefficient. The second is no involvement of heterogeneous decision-makers (DMs), possibly end-users as stakeholders apart from the experts. To address the first issue, a novel threshold-based feedback mechanism is introduced to improve the efficiency of the CRP that helps the experts reach consensus in at most one round of feedback. To address the second issue, end-users are invited to participate in decision-making where their majority group opinion is used. Then, a novel concept of tolerance degree of the moderator is proposed to obtain the final decision considering the consensual opinion of experts and cumulative opinion of end-users. The effectiveness of the proposed method is demonstrated through a case of healthcare service selection. Further, various experiments are conducted to show how the proposed work outperforms the existing works. © 2023 World Scientific Publishing Company.